Quantitative analysis of Sudan dye adulteration in paprika powder using FTIR spectroscopy. Issue 5 (4th May 2017) - Lohumi, Santosh; Joshi, Ritu; Kandpal, Lalit Mohan; Lee, Hoonsoo; Kim, Moon S.; Cho, Hyunjeong; Mo, Changyeun; Seo, Young-Wook; Rahman, Anisur; Cho, Byoung-Kwan
ABSTRACT: As adulteration of foodstuffs with Sudan dye, especially paprika- and chilli-containing products, has been reported with some frequency, this issue has become one focal point for addressing food safety. FTIR spectroscopy has been used extensively as an analytical method for quality control and safety determination for food products. Thus, the use of FTIR spectroscopy for rapid determination of Sudan dye in paprika powder was investigated in this study. A net analyte signal (NAS)-based methodology, named HLA/GO (hybrid linear analysis in the literature), was applied to FTIR spectral data to predict Sudan dye concentration. The calibration and validation sets were designed to evaluate the performance of the multivariate method. The obtained results had a high determination coefficient ( R 2 ) of 0.98 and low root mean square error (RMSE) of 0.026% for the calibration set, and an R 2 of 0.97 and RMSE of 0.05% for the validation set. The model was further validated using a second validation set and through the figures of merit, such as sensitivity, selectivity, and limits of detection and quantification. The proposed technique of FTIR combined with HLA/GO is rapid, simple and low cost, making this approach advantageous when compared with the main alternative methods based on liquid chromatography (LC) techniques. GRAPHICAL ABSTRACT: